(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article considers the paremies with biblical names-symbols, which have lost the direct connections with biblical-philosophical sense of concepts, as the result the permanent complexes get national-colloquial character, the estimating characteristics are removing, the everyday vision of images appears; the problem of non-combination of the biblical moral postulates and collective ethnic experience, accumulated in the paremies, is raised here.